1988
DOI: 10.1007/bf00277409
|View full text |Cite
|
Sign up to set email alerts
|

Artificial induction of intravascular lipolysis by lipid-heparin infusion leads to insulin resistance in man

Abstract: Although extensive evidence indicates that free fatty acids can decrease glucose utilization in vitro, it is still controversial how an increase in lipolysis affects glucose metabolism in man. To test the hypothesis that an increase in lipolysis is related to insulin resistance, we examined the effect of lipid-heparin infusion on glucose metabolism in ten normal subjects by the euglycaemic glucose clamp technique and isotopic determination of glucose turnover. In the control euglycaemic clamp studies with insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Other studies showed that the lipid induced inhibition of insulin stimulated glucose uptake was linear (14,15) "figure 3" and occurred similarly in healthy subjects and in patients with Type II diabetes (14)(15)(16)(17)(18)(19)(20). The long delay of 3-4 hours between the start of the insulin and lipid infusions and the development of significant insulin resistance was the most likely reason why the inhibitory effect of FFA on glucose uptake was not found in many previous studies (21)(22)(23)(24)(25).…”
Section: Effect Of Ffa On Insulin Stimulated Glucose Uptakementioning
confidence: 85%
“…Other studies showed that the lipid induced inhibition of insulin stimulated glucose uptake was linear (14,15) "figure 3" and occurred similarly in healthy subjects and in patients with Type II diabetes (14)(15)(16)(17)(18)(19)(20). The long delay of 3-4 hours between the start of the insulin and lipid infusions and the development of significant insulin resistance was the most likely reason why the inhibitory effect of FFA on glucose uptake was not found in many previous studies (21)(22)(23)(24)(25).…”
Section: Effect Of Ffa On Insulin Stimulated Glucose Uptakementioning
confidence: 85%